2015
DOI: 10.3892/mmr.2015.4252
|View full text |Cite
|
Sign up to set email alerts
|

Fucoidan inhibits proliferation of the SKM-1 acute myeloid leukaemia cell line via the activation of apoptotic pathways and production of reactive oxygen species

Abstract: Myelodysplastic syndromes (MDS) are a heterogeneous group of myeloid disorders characterized by peripheral blood cytopenias and a high risk of progression to acute myeloid leukaemia (AML). Fucoidan, a complex sulphated polysaccharide isolated from the cell wall of brown seaweeds, has recently attracted attention for its multiple biological activities and its potential as a novel candidate for cancer therapy. In the present study, the anti-cancer activity of fucoidan was investigated in the MDS/AML cell line SK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 30 publications
2
25
0
Order By: Relevance
“…Moreover, proapoptotic BAX, cleaved caspase-3, and cleaved PARP1 increased while BCL2 decreased upon fucoidan treatment of HT29 cells, stimulating cell death. These results are supported by previous studies in which fucoidan inhibited proliferation of myeloid leukemia cell lines, mediated by activation of apoptotic pathways (21). Therefore, our results strongly suggest that fucoidan plays an ANTICANCER RESEARCH 36: 4449-4458 (2016) 4454 important role in HT29 cell-cycle arrest and apoptosis.…”
Section: Effect Of Fucoidan On Ht29 Colon Cancer Cell Apoptosis Htsupporting
confidence: 91%
“…Moreover, proapoptotic BAX, cleaved caspase-3, and cleaved PARP1 increased while BCL2 decreased upon fucoidan treatment of HT29 cells, stimulating cell death. These results are supported by previous studies in which fucoidan inhibited proliferation of myeloid leukemia cell lines, mediated by activation of apoptotic pathways (21). Therefore, our results strongly suggest that fucoidan plays an ANTICANCER RESEARCH 36: 4449-4458 (2016) 4454 important role in HT29 cell-cycle arrest and apoptosis.…”
Section: Effect Of Fucoidan On Ht29 Colon Cancer Cell Apoptosis Htsupporting
confidence: 91%
“…Importantly, we demonstrated that fucoidan induces ROS in a very short period (within 30 min). In contrast, fucoidan has been reported to promote mitochondrial-derived ROS generation after approximately 24–48 h25. Thus, the fucoidan-induced increase in ROS may occur at an early stage (receptor-mediated) or at a later stage (mitochondria-derived).…”
Section: Discussionmentioning
confidence: 95%
“…However, there are many “factors” of fucoidan involved in anti-cancer functions; for example, sources of fucoidan (species of brown seaweeds)232425, effective concentration, structural characteristics, sulfate content, molecular weight, purity, isolation/extraction methods, etc., as well as importantly the kind of cancer cells to be tested. Here, using HiQ-fucoidan from Laminaria japonica , we found that fucoidan also prevents and inhibits lung tumor growth at higher concentrations (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has shown that in contrast to the tumor-promoting ability of higher ROS levels, this biochemical property of cancer cells may have therapeutic benefits. Targeting mitochondria to increase the ROS level above a toxic threshold by exogenous ROS-generating phytochemicals to selectively kill cancer cells has been shown to be feasible in various in vitro and in vivo experimental models [29][30][31][32][33] . In the present study, TBMS1 increased ROS generation, modulated Bax and Bcl-2 expression, dissipated mitochondrial membrane potential and ultimately induced apoptosis in DU145 cells by inducing DNA fragmentation and caspase-3 cleavage in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%